Technological innovation for sustainable development: an analysis of different types of impacts for countries in the BRICS and G7 groups - Santana, Naja Brandao; Do Nascimento Rebelatto, Daisy Aparecida; Perico, Ana Elisa [UNESP]; Moralles, Herick Fernando; Leal Filho, Walter (Taylor & Francis Inc, 2015)
Technological innovation is considered as being one of the major driving forces in fostering economic growth. However, in the current economic situation, where matters related to environmental protection and conservation play a key role, technological innovation can also be used as a driver of new production alternatives to reduce the harmful impacts of industrial development on society and nature. Within this context, this paper aims to analyze, through econometric tools, the relationship between investments in technological innovation and the sustainable development of G7 and BRICS countries. The results demonstrate that for the BRICS group, technological innovation has been significant for the three pillars of sustainable development. However, for the G7 group, technological innovation was considered significant only for social development, showing no statistical significance for economic and environmental development. The results indicate that technological innovation can cause different types of impacts, depending on the development stage of the analyzed country or region.
Keywords: BRICS; G7; sustainable development; economic growth; technological innovation